PEMASARAN IKAN SEGAR AIR TAWAR DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Sukardi Sukardi (Jurnal Perikanan Universitas Gadjah Mada, 2001)
The special region province of Yogyakarta (DIY) has  five regencies with different natural resources to support the development of fishery product. Therefore, fishery product especially fish was distributed from surplus regencies to the other regencies which produced less quantity of the product. The objectives of this study were to know the market structure, market channel, price margin and fluctuation. The study was conducted using analytic discriptive method. Data were collected by survey in 5 regencies in DIY province, covered subjects such as wholesaler, retailer, dealer, farmer (producer) and consumer. Results of this study indicated that (1) market structure in wholesaler level was oligopoly, but in the retailer level was free market. The retailers had stronger relationship to wholesaler  specially for keeping continuity of fish supply, (2) fish market channel and price margin depending on fish species and location of markets, (3) prices fluctuation was determined by supply and demand mechanism. The average price margins in wholesalers and retailer ranged from  10  to 15 and 10 to 20%,  respectively,  (4)  marketing of fresh freshwater fishes were still consentrated in the city and its surrounding area. Comparing with the other regencies in DIY, Yogyakarta Regency (Kotamadya Yogyakarta) had the largest demand for freshwaterfish which was dominated by cat fish (lele dumbo).